Propensity for Calcification in Serum Associates With 2-Year Cardiovascular Mortality in Ischemic Heart Failure With Reduced Ejection Fraction - Bojic, Marija; Koller, Lorenz; Cejka, Daniel; Niessner, Alexander; Bielesz, Bernhard (Frontiers in Medicine, 2021)
Background The propensity of serum to calcify, as assessed by the T50-test, associates with mortality in patients with chronic kidney disease. In chronic heart failure, phosphate and fibroblast growth factor-23 (FGF-23), which are important components of the vascular calcification pathway, have been linked to patient survival. Here, we investigated whether T50 associates with overall and cardiovascular survival in patients with chronic heart failure with reduced ejection fraction (HFrEF). Methods We measured T50, intact and c-terminal FGF-23 levels in a cohort of 306 HFrEF patients. Associations with overall and cardiovascular mortality were analyzed in survival analysis and Cox-regression models. Results After a median follow-up time of 3.2 years (25th – 75th percentile: 2.0 – 4.9 years), 114 patients (37.3%) died due to any cause and 76 patients (24.8%) died due to cardiovascular causes. 139 patients (45.4%) had ischemic and 167 patients (54.6%) had non-ischemic HFrEF. Patients with ischemic HFrEF in the lowest T50-tertile had significantly greater 2-year cardiovascular mortality compared to patients in higher tertiles (p=0.011). In ischemic but not in non-ischemic HFrEF, T50 was significantly associated with cardiovascular mortality in univariate (p=0.041) and fully adjusted (p=0.046) Cox regression analysis. Significant associations of intact and c-terminal FGF-23 with all-cause and cardiovascular mortality in univariate Cox regression analysis did not remain significant after adjustment for confounding factors. Conclusion T50 is associated with 2-year cardiovascular mortality in patients with ischemic HFrEF but not in non-ischemic HFrEF. More research on the role of T50 measurements in coronary artery disease is warranted.